An investigation of the teaching of writing in Grade-9 English first-language classrooms: a case study of a selected government school in Namibia - Martins, Simone Alexandra Domingues (Rhodes University, Faculty of Education, Department of Education, 2019)
The pedagogical practice choices teachers make when teaching writing in Grade-9 English first- language classrooms, as well as the extent to which these pedagogical practices appear to enable or constrain learners' acquisition of writing skills as per grade-specific curricular expectations, are the focus of the study. It draws from Bernstein's (1971) curriculum and society theory, as well as genre theory. Located within the qualitative case study approach, it is designed to investigate the reasons for Grade-9 English first-language learners' underperformance in Paper 2, the composition component of the Namibian external examinations. Drawing from the interpretivist paradigm, the study uses one-on-one interviews, semi-structured classroom observations, as well as documentary evidence of the Namibian English first-language syllabus and examples of learners' written work, to generate data. The research site and study participants were purposefully selected. The study involves two Grade-9 English first-language teachers and classrooms at one Namibian High School, and took place from the second to the third terms of 2017.
Keywords: English language -- Rhetoric -- Study and teaching -- Namibia; English language -- Study and teaching (Secondary) -- Namibia; English language == Composition and exercises -- Study and teaching (Secondary) -- Namibia